Local recurrence risk after previous salvage mastectomy. Issue 7 (July 2016) - Tanabe, M.; Iwase, T.; Okumura, Y.; Yoshida, A.; Masuda, N.; Nakatsukasa, K.; Shien, T.; Tanaka, S.; Komoike, Y.; Taguchi, T.; Arima, N.; Nishimura, R.; et al.
Abstract: Introduction: Breast-conserving surgery is a standard treatment for early breast cancer. For ipsilateral breast tumor recurrence (IBTR) after breast-conserving surgery, salvage mastectomy is the current standard surgical procedure. However, it is not rare for patients with IBTR who have received salvage mastectomy to develop local recurrence. In this study, we examined the risk factors of local recurrence after salvage mastectomy for IBTR. Patients and methods: A total of 118 consecutive patients who had histologically confirmed IBTR without distant metastases and underwent salvage mastectomy without irradiation for IBTR between 1989 and 2008 were included from eight institutions in Japan. The risk factors of local recurrence were assessed. Results: The median follow-up period from salvage mastectomy for IBTR was 4.6 years. Patients with pN2 or higher on diagnosis of the primary tumor showed significantly poorer local recurrence-free survival than those with pN0 or pN1 at primary tumor (p < 0.001). Multivariate analysis showed that the lymph node status of the primary tumor was a significantly independent predictive factor of local recurrence-free survival (p = 0.02). Conclusion: The lymph node status of the primary tumor might be a predictive factor of local recurrence-free survival after salvage mastectomy for IBTR. Further research and validation studies are needed. (UMIN-CTR number UMIN000008136).